2013
DOI: 10.1103/physreve.87.032164
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations and correlations of a driven tracer in a hard-core lattice gas

Abstract: We consider a driven tracer particle (TP) in a bath of hard-core particles undergoing continuous exchanges with a reservoir. We develop an analytical framework which allows us to go beyond the standard force-velocity relation used for this minimal model of active microrheology and quantitatively analyze, for any density of the bath particles, the fluctuations of the TP position and their correlations with the occupation number of the bath particles. We obtain an exact Einstein-type relation which links these f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…(5), we first solve Eq. (14) in Fourier space and then we insert the result in Eq. (15), taking the limit of small k and ω.…”
Section: Solution Of the Master Equation For The Lévy Walkmentioning
confidence: 99%
“…(5), we first solve Eq. (14) in Fourier space and then we insert the result in Eq. (15), taking the limit of small k and ω.…”
Section: Solution Of the Master Equation For The Lévy Walkmentioning
confidence: 99%
“…[24] it is shown that the position distribution converges to a Gaussian distribution. Its variance may however exhibit anomalous growth depending on the geometry [24][25][26]. In particular, for a quasi-1D narrow channel it has been shown that at large densities the position distribution of a tracer in a symmetric lattice gas converges to a Gaussian with variance ≃ t 3/2 , a strongly superdiffusive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the linear response regime, a fundamental result is the fluctuationdissipation theorem, which relates system response and spontaneous fluctuations. Within the last years a great effort has been devoted to generalizations of this theorem to nonequilibrium situations [1][2][3][4], when the time reversal symmetry is broken, and also to elucidating the effects of the higher order contributions in the external perturbation [5][6][7][8][9][10][11]. From experimental perspective, theoretical understanding of the latter issues is of an utmost importance in several fields, such as active microrheology [12][13][14] and dynamics of nonequilibrium fluids [15,16].…”
mentioning
confidence: 99%